Functional Comparison of 45 Naturally Occurring Isoforms of the Plasmodium falciparum Chloroquine Resistance Transporter (PfCRT) - Callaghan, Paul S. (Biochemistry, 2015)
At least 53 distinct isoforms of Plasmodium falciparum chloroquine resistance transporter (PfCRT) protein are expressed in strains or isolates of P. falciparum malarial parasites from around the globe. These parasites exhibit a range of sensitivities to chloroquine (CQ) and other drugs. Mutant PfCRT is believed to confer cytostatic CQ resistance (CQR(CS)) by transporting CQ away from its DV target (free heme released upon hemoglobin digestion). One theory is that variable CQ transport catalyzed by these different PfCRT isoforms is responsible for the range of CQ sensitivities now found for P. falciparum. Alternatively, additional mutations in drug-selected parasites, or additional functions of PfCRT, might complement PfCRT-mediated CQ transport in conferring the range of observed resistance phenotypes. To distinguish between these possibilities, we recently optimized a convenient method for measuring PfCRT-mediated CQ transport, involving heterologous expression in Saccharomyces cerevisiae. Here, we use this method to quantify drug transport activity for 45 of 53 of the naturally occurring PfCRT isoforms. Data show that variable levels of CQR likely depend upon either additional PfCRT functions or additional genetic events, including perhaps changes that influence DV membrane potential. The data also suggest that the common K76T PfCRT mutation that is often used to distinguish a P. falciparum CQR phenotype is not, in and of itself, a fully reliable indicator of CQR status.